Evaluation on The Supplementation of Fermented Garlic Extract in Protecting Human Lymphocytes In Vitro From The Negative Impact of Gamma-Rays - Syaifudin, Mukh; Adha, Nila Dariska; Purnami, Sofiati; Wulyoadi, Sasmito; Marwanto, Edy; Suyanto, Suyanto; Marasabessy, Ahmad; Herianto, Gany; Tetriana, Devita (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2017)
Garlic (Allium sativum) contains a wide range of phytocompounds that produce various responses in human body. However the knowledge on the potential of fermented form of garlic in protecting negative impacts of radiation is very limited. In this research in vitro efficacy of fermented garlic in protecting negative impact of gamma ray was studied using cytogenetic test. A set of culture of human lymphocytes was irradiated with 60Co gamma rays at dose of 2 Gy (dose rate of 2 Gy/min) and fermented garlic extract at four working concentrations of 0, 125, 250 and 500 mg/mL were added to these cells and then were incubated at 37oC for 48 hrs. Colcemid was added at 3 hr before harvest to collect metaphase cells and it was done by standard methodology for cytogenetic analysis. The fermented garlic extract significantly (p<0.05) did not exhibited antigenotoxic effect of gamma rays and its effectiveness was same as in control (without extract treatment) group. In contrary all concentration of chemicals (125, 250 and 500 mg/mL) were seemingly tend to induce higher number of dicentric and fragment chromosomes than control under microscopic observation. Mitotic index of the cell that was determined with programmed metaphase finder also did not influenced by garlic addition. It was concluded that aqueous garlic extract did not possesses its efficacy in protecting impact of ionizing radiation.